Comparative electromechanical and hemodynamic effects of left ventricular and biventricular pacing in dyssynchronous heart failure: electrical resynchronization versus left-right ventricular interaction - Lumens, Joost (2013)
OBJECTIVES: To enhance understanding of the working mechanism of cardiac resynchronization therapy (CRT) by comparing animal experimental, clinical, and computational data on the hemodynamic and electromechanical consequences of left ventricular and biventricular pacing (LVP and BiVP, respectively). BACKGROUND: It is unclear why LVP and BiVP have comparative positive effects on hemodynamic function of patients with dyssynchronous heart failure (HF). METHODS: Hemodynamic response to LVP and BiVP (%-change LVdP/dt(max)) was measured in 6 dogs and 24 patients with HF and left-bundle branch block (LBBB), followed by computer simulations of local myofiber mechanics during LVP and BiVP in the failing heart with LBBB. Pacing-induced changes of electrical activation were measured in dogs using contact mapping and in patients using a noninvasive multielectrode electrocardiographic mapping technique. RESULTS: LVP and BiVP similarly increased LVdP/dt(max) in dogs and in patients, but only BiVP significantly decreased electrical dyssynchrony. In the simulations, LVP and BiVP increased total ventricular myofiber work to the same extent. While the LVP-induced increase was entirely due to enhanced right ventricular (RV) myofiber work, the BiVP-induced increase was due to enhanced myofiber work of both the LV and RV. Overall, LVdP/dt(max) correlated better with total ventricular myofiber work than with LV or RV myofiber work alone. CONCLUSIONS: Experimental, human, and computational data support the similarity of hemodynamic response to LVP and BiVP, despite differences in electrical dyssynchrony. The simulations provide the novel insight that, through ventricular interaction, the RV myocardium importantly contributes to the improvement in LV pump function induced by CRT.